THE IMPACT AND INTERACTION OF METABOLIC ELEMENTS ON LEFT ATRIAL STIFFNESS IN HYPERTENSION. (June 2022) - Liu, Yan; Sun, Qiaobing; Fu, Tingting; Pan, Yu; Sun, Yancui; Jiang, Yinong
Abstract : Objective: To evaluate left atrial (LA) stiffness using two-dimensional speckle-tracking echocardiography (2DSTE) and investigate the impact and interaction of metabolic elements on LA stiffness index (LASI). Design and method: 340 subjects were enrolled and divided into three groups: Group I (n = 38), healthy controls; Group II (n = 138), hypertension without metabolic syndrome (MS); Group III (n = 164), hypertension with MS. All subjects were performed LA phasic strains using 2DSTE, and the following parameters were measured: LA reservoir strain and strain rate (LAS-S, LASR-S), LA conduit strain and strain rate (LAS-E and LASR-E), LA booster strain and strain rate (LAS-A and LASR-A). The LASI was defined as the ratio of early diastolic transmitral flow velocity/lateral mitral annulus myocardial velocity (E/e') to LAS-S. Binary logistic regression models were performed, and the odds ratios (OR) at 95% confidence interval (CIs) were used to approximate the associated risk of the elements of MS (obesity, diabetes and dyslipidaemia) for LA stiffness, with the lowest binary serving as the reference category. Results: LASI was significantly higher in Group II (0.34 ± 0.21) than Group I (0.19 ± 0.04) (p < 0.001), and further increased in Group III (0.39 ± 0.22) (p < 0.001). LA reservoir and conduit functions gradually and significantly decreased from Group I to Group III (p < 0.001). However, there were no significant differences in LA booster pump function among three groups (p> 0.05). Regarding the elements of MS, body mass index (BMI), hemoglobin A1c (HbA1c) and triglyceride (TG) were positively associated with LASI. Furthermore, we performed the interaction analyses between two of the three elements of MS (BMI, HbA1c and TG). We simultaneously stratified both elements into equal-sized binaries of their individual distribution and then showed that compared with the lowest risk reference group, risk for LA stiffness significantly increased in other groups (Figure). Conclusions: LA phasic function was impaired and LA stiffness was increased in hypertensive patients with MS. Elements of MS (BMI, HbA1c and TG levels) had independent and interaction effect on LA stiffness in hypertension.